2012
DOI: 10.1503/jpn.110109
|View full text |Cite
|
Sign up to set email alerts
|

Association between the NMDA glutamate receptor GRIN2B gene and obsessive–compulsive disorder

Abstract: Background: Recent data from neuroimaging, genetic and clinical trials and animal models suggest a role for altered glutamatergic neuro transmission in the pathogenesis of obsessive-compulsive disorder (OCD). The aim of this study was to investigate whether variants in the GRIN2B gene, the gene encoding the NR2 subunit of the N-methyl-D-aspartate (NMDA) glutamate receptor, may contribute to genetic susceptibility to OCD or to different OCD subphenotypes. Methods: Between 2003 and 2008, we performed a case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 63 publications
2
29
0
1
Order By: Relevance
“…In addition to the glutamate transporter the N-methyl-D-aspartate (NMDA) receptors, a class of ionotropic glutamate receptors, are of special interest in OCD. Not only that NMDA receptor gene variants were suggested to associate with OCD (Alonso et al, 2012), dysfunction of NMDA receptors neurotransmission activity were suggested to be involved in OCD (Richter et al, 2012) as well as to mediate fear conditions (Davis, 2011). The NMDA receptor channels are heteromers, composed of three different subunits: NR1 (GRIN1), NR2 (GRIN2A, GRIN2B, GRIN2C, or GRIN2D).…”
Section: The Glutamatergic Systemmentioning
confidence: 99%
“…In addition to the glutamate transporter the N-methyl-D-aspartate (NMDA) receptors, a class of ionotropic glutamate receptors, are of special interest in OCD. Not only that NMDA receptor gene variants were suggested to associate with OCD (Alonso et al, 2012), dysfunction of NMDA receptors neurotransmission activity were suggested to be involved in OCD (Richter et al, 2012) as well as to mediate fear conditions (Davis, 2011). The NMDA receptor channels are heteromers, composed of three different subunits: NR1 (GRIN1), NR2 (GRIN2A, GRIN2B, GRIN2C, or GRIN2D).…”
Section: The Glutamatergic Systemmentioning
confidence: 99%
“…Additional candidate genes in the glutamate system have also been studied, including GRIN2B , which shows evidence of association in some but not all studies (Arnold et al, 2004, Alonso et al, 2012, Cai et al, 2013). The other leading candidate gene is the serotonin transporter, SLC6A4 , with both common and rare variants exhibiting association in some studies (Ozaki et al, 2003, Dickel et al, 2007, Grados et al, 2007, Saiz et al, 2008, Wendland et al, 2008), but not all (Taylor, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variations in NMDA receptors have been implicated in the genetic susceptibility to neurological, psychiatric and learning disorders, e.g. obsessive-compulsive disorder [12], attention deficit/hyperactivity disorder (ADHD) [13], dyslexia [14], schizophrenia and bipolar disorders [15], Parkinson disease and Huntington disease [16]. It is still an open debate whether patients with GRIN2B mutations present with an unspecific ID phenotype with some anomalies in behavior, or with a very specific behavioral phenotype that could lead to the suspicion of a GRIN2B mutation on clinical evidence alone.…”
Section: Introductionmentioning
confidence: 99%